Intestinal absorption and distribution of naringin, hesperidin, and their metabolites in mice. (November 2020) - Guo, Xiao; Li, Kaikai; Guo, Ailing; Li, Erhu
Graphical abstract: Highlights: Naringin and hesperidin, and their metabolites were found to be widely absorbed in the intestinal tissue. Both naringin and hesperidin have different bioavailability in each intestinal tissue. There were different metabolites distributed in different intestinal tissues. Abstract: In this study, an in vivo animal experiment was performed, to investigate the intestinal absorption and distribution of naringin, hesperidin, and their metabolites by using UPLC-ESI-MS/MS and HPLC-PDA analysis. The bioavailability of naringin or hesperidin in duodenum, jejunum, ileum, cecum, and colon was calculated. A total of 7 and 13 metabolites were found and tentatively identified in intestinal tissue after orally administered naringin and hesperidin in mice, respectively. Sulfates of naringin could be absorbed by ileum and cecum, de-glycosylation metabolites could be absorbed by duodenum, and phenolic acids could be absorbed by the cecum and colon. Sulfates of hesperidin could be absorbed by duodenum and ileum, de-glycosylation metabolites could be absorbed by cecum, and phenolic acids could be absorbed by ileum, cecum and colon. Jejunum did not absorb metabolites of naringin or hesperidin. Results could be beneficial for understanding the intestinal bioactivities of naringin and hesperidin.